Insulin resistance among obese middle-aged is associated with decreased cerebrovascular reactivity. (18th July 2017) - Frosch, Olivia H.; Yau, Po Lai; Osorio, Ricardo S.; Rusinek, Henry; Storey, Pippa; Convit, Antonio
Abstract : Objective: To evaluate differences in cerebrovascular reactivity (CVR) to mild hypercapnia in obese/overweight individuals with and without insulin resistance (IR) compared to comparable lean controls. Methods: A total of 60 cognitively normal participants (20 lean controls and 24 obese/overweight individuals with and 16 without IR) were evaluated using a high spatial resolution arterial spin labeling MRI technique at rest and during mild hypercapnia. We analyzed group differences in CVR in cerebral cortex and ascertained the relationships between CVR, IR, and body mass index (BMI). Results: Obese/overweight participants with and without IR had significantly lower CVR to hypercapnia than lean controls after controlling for age, sex, and the presence of hypertension ( F 2, 53 = 5.578, p = 0.006 = 0.174). In the obese/overweight participants with IR, there was a significant correlation between higher CVR and a measure of insulin sensitivity, even after accounting for BMI ( r p = 0.575, p = 0.004). In contrast, there was no relationship between CVR and BMI when controlling for IR. No such relationships existed for the other 2 groups. Conclusions: IR is associated with impaired CVR; the relationship appears to be driven by the degree of IR and not by obesity. These rarely reported results suggest that early forms of cerebrovascular dysfunction exist among obese middle-aged individuals with significant IR but without type 2 diabetes mellitus. These functional vascular abnormalities may help explain the associations among IR, diabetes, and dementia, and suggest that interventions aiming to improve IR or CVR may help prevent cognitive decline later in life.